Differentially Expressed miRNAs Influence Metabolic Processes in Pituitary Oncocytoma - Krokker, Lilla (Neurochem Res, 2019)
Spindle cell oncocytomas (SCO) of the pituitary are rare tumors accounting for 0.1–0.4% of all sellar tumors. Due to their rarity, little information is available regarding their pathogenesis. Our aim was to investigate miRNA expression profile of pituitary oncocytomas. Total RNA was extracted from 9 formalin-fixed paraffin embedded pituitary samples (4 primary, 3 recurrent oncocytomas and 2 normal tissues). Next-generation sequencing was performed for miRNA profiling. Transcriptome data of additional 6 samples’ were obtained from NBCI GEO database for gene expression reanalysis and tissue-specific target prediction. Bioinformatical analysis, in vitro miRNA mimics transfection, luciferase reporter system and AlamarBlue assay were applied to characterize miRNA’s function. 54 differentially expressed miRNAs and 485 genes in pituitary SCO vs. normal tissue and 8 miRNAs in recurrent vs. primary SCO were determined. Global miRNA downregulation and decreased level of DROSHA were detected in SCO samples vs. normal tissue. Transcriptome analysis revealed cell cycle alterations while miRNAs influenced mainly metabolic processes (tricarboxylic acid cycle-TCA, carbohydrate, lipid metabolism). Through miRNA-target interaction network the overexpressed Aconitase 2 potentially targeted by two downregulated miRNAs (miR-744-5p, miR-127-3p) was revealed. ACO2 and miR-744-5p interaction was validated by luciferase assay. MiR-127-3p and miR-744-5p significantly decreased cell proliferation in vitro. Our study firstly reported miRNA profile of pituitary oncocytoma. Our results suggest that tumor suppressor miRNAs may have an essential role in the pathogenesis of pituitary oncocytoma. Earlier reports showed downregulated TCA cycle in SCO which is extended by our results adding the role of miR-744-5p targeting ACO2. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11064-019-02789-2) contains supplementary material, which is available to authorized users.